Calculation Method to Analize The Concordance Between Supply and Demand of Bus Public Transport For Morning Commuter Trip at Gubeng Station - Jos Oktarina Pratiwi; Hitapriya Suprayitno (IPTEK Journal of Proceedings Series, 2015)
Surabaya is the center of activity for the province of East Java and eastern Indonesia. Commuting to Surabaya is very high. Thus, the concordance between supply and demand of public transport for commuter trip must be evaluated. For this purpose a calculation method has to be developed. The research objective has been achieved. The method calculation based on special matrix technics for overlay calculation.